Prevalence and risk factors of self-medication in pregnancy: A cross-sectional study from a tertiary care hospital in Eastern India - Gupta, Mayank; Dalai, Chanchal Kumar; Ahmed, Shah Newaz; Sarkar, Deblina; UR, Rajath Rao; Nirala, Santosh Kumar (Asian Journal of Medical Sciences, 2021)
Background: Self-medication in pregnancy is a common but unsafe practice. There is a possibility of surreptitious exposure of the developing fetus to the teratogenic and abortifacient effects of the drugs. Aims and Objectives: In this study, we assessed the prevalence and risk factors of self-medication in pregnant mothers visiting the antenatal clinic in our hospital. Materials and Methods: A standard questionnaire seeking information on the socio-demographic profile, clinical characteristics, laboratory data, and knowledge and habits was administered to the pregnant mothers (n=190). The risk factors of self-medication were determined using Fischer’s exact test. P<0.05 was deemed statistically significant. Results: The prevalence of self-medication in pregnancy was found to be 6.3%. Low education level (P<0.027), employed women (P<0.031), and history of miscarriage (P<0.036) in the previous pregnancy were the main determinants of self-medication in the present pregnancy. Conclusion: The prevalence of self-medication in the study sample was low as compared to contemporary studies. High literacy (94.2%) and easy availability of health facility (98%) may be the possible reasons. Further studies are warranted to confirm the prevalence and risk factors of self-medication in this part of the country.